Effective dipole model for electrostatic interactions between polarizable spherical particles in particle scale simulations - Maria Giordano; Francesca O. Alfano; Francesco P. Di Maio; Alberto Di Renzo (Scientific Reports)
Abstract Despite their widespread adoption, particle-scale simulation methods, such as the Discrete Element Method (DEM), for electrically charged particles in several natural processes and industrial transformations do not include realistic polarization effects. At close distances, these can dominate the particle motion and are impossible to predict by the commonly adopted Coulomb point-charge approximation. Sophisticated mathematical tools can account for uneven charge distributions, predicting an attractive force between a charged particle and a neutral particle or possible attraction between two like-charged particles. Such approaches are accurate but too complex for implementation in DEM simulations of many interacting particles. We propose a novel, simpler yet realistically accurate effective dipole model. By attributing a net charge and an induced effective dipole to each sphere, the interaction force between charged polarizable particles is computed in closed form. A comparison of a rigorous solution and the proposed dipole approach for two spherical particles reveals significant improvement over the commonly employed Coulomb law. The effects of particle size ratio and charge ratio on the interaction force are discussed. Then, the dynamic DEM simulation of a shaker filled with a binary mixture of differently sized particles that are all positively charged is shown to predict the counterintuitive formation of fine-on-coarse aggregates.